Media effects Theory and research. [article]. - Valkenburg, Patti M.
As the proverbial creatures of habit, people tend to repeat the same behaviors in recurring contexts. This review characterizes habits in terms of their cognitive, motivational, and neurobiological properties. Inso doing, we identify three ways that habits interface with deliberate goal pursuit : First, habits form as people pursue goals by repeating the same responses in a given context. Second, as outline in computational models, habits and deliberate goal pursuit guide actions synergistically, although habits are the efficient, default mode of response. Third, people tend to infer from the frequency of habit performance that the behavior must have been intended. We conclude by applying insights from habit research to understand stress and addiction as well as the design of effective interventions to change health and consumer behaviors. -- (from the authors)